Victim identification from the September 11, 2001 attack on the World Trade Center: Past trends and future projections. (November 2022) - Adams, Bradley; Warnke-Sommer, Julia; Odien, Jennifer; Soler, Angela; Damann, Franklin
Abstract: Victim identification following mass fatality events is critically important. Extensive traumatic injuries and body fragmentation add complexity to this process. World Trade Center (WTC) identification efforts have been ongoing for over 20 years and this study tracks identification trends from the 2753 known WTC victims and the 21, 905 recovered remains. For identified victims, data include the number of remains identified, date(s) of the identification(s), and identification modalities. Results show a heavy reliance on DNA due to body fragmentation. Other modalities played an important role initially, but DNA eventually became the singular identification modality. For large-scale disasters involving significant body fragmentation, aggressive DNA testing strategies are critical for victim identification. Over time, the number of linked remains (portions of previously identified individuals) will greatly outnumber the new identifications (first-time identifications). A novel approach using statistical modeling from ecology studies was applied to estimate future WTC identification rates using Identification Accumulation Curve extrapolation with the Good-Toulmin estimator. Projections indicate there will be 76 first-time identifications (95% CI: 49–117) through the successful DNA testing of 3404 unidentified, fragmentary remains. The remainder of the identifications would be additional portions of previously identified victims. These results may be instructional for management of other large-scale, protracted victim identification efforts. Highlights: 20 years of victim identification data from the WTC disaster in NYC were analyzed to observe identification trends. Other modalities played a role initially, but DNA eventually became the singular identification modality. With high body fragmentation, the number of linked remains will greatly outnumber the new identifications over time. Modeling from ecology studies was applied to estimate future WTC identification rates.